Employee Voice and Perceived Organisational Performance in Manufacturing Industries in Dar es Salaam, Tanzania: Mediation Effect of Employee Absenteeism and Labour Turnover (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2026)
Despite extensive studies on the relationship between employee voice and organisational performance, little is known about how this relationship varies based on the situation. Therefore, this study examines the influence of employees' voices on perceived organisational performance in manufacturing industries in Dar es Salaam, Tanzania, with employee absenteeism and labour turnover as mediating variables. A cross-sectional study design was employed, with human resource managers as the unit of observation and manufacturing industries as the unit of analysis. Data for the survey came from 126 manufacturing companies in Dar es Salaam, Tanzania. Descriptive statistics and partial least squares structural equation modelling (PLS-SEM) were used to analyse the data. The results show that employee voice has a significant positive effect on organisational performance (β = 0.409, p = 0.009) and a negative effect on employee absenteeism (β = -1.595, p = 0.000) and labour turnover (β = -0.442, p = 0.029). Furthermore, employee absenteeism exerts a significant partial mediating effect on the relationship between employee voice and perceived organisational performance (β = 1.136, p < 0.05), but not on labour turnover (β = 0.001, p > 0.05). The study concludes that employee voice significantly enhances performance both directly and indirectly by reducing employee absenteeism. The findings suggest that manufacturing industries should use employee voice mechanisms to encourage presenteeism in order to improve their performance.